Discipline as a key factor in the formation of legal awareness and legality among Ukrainian citizens - Dziubak S. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to analyze the phenomenon of discipline as a factor influencing the formation of legal awareness and legality among citizens of Ukraine, to reveal their interrelationship and interdependence. Methodology. The methodology involves a complex analysis and generalization of the available scientific and theoretical data, as well as the formulation of relevant conclusions and recommendations. The following methods of scientific knowledge were used during the research: terminological, comparative, comparative, systemic-structural, formal-logical. Results. In the research process, it was recognized that the discipline in scientific sources is considered as a system of norms and rules of behavior that ensures compliance with the standards of morality and law accepted in society. Discipline, as the timely and proper fulfillment of rules and obligations, is an important component of legality, as it contributes to the formation of legal awareness and ensuring law and order in the state, as well as stimulates citizens to comply with the adopted laws and norms of life. A high level of discipline in society and organizations is a guarantee of stable law and order and the development of the rule of law, which is especially important for Ukraine in modern conditions. Originality. of the study consists in identifying and substantiating the significant role of discipline in the formation of legal consciousness of citizens, which plays an important role in ensuring law and order and legality in the country. In the process of research, it was established that these new concepts expand our understanding of the influence of discipline on legal regulation and provide practical recommendations for improving legal culture and the effectiveness of law enforcement activities in Ukraine. Practical significance. The results of the study can be used in their potential application to improve the legal system and law enforcement processes.